2016
DOI: 10.5860/crl.77.4.520
|View full text |Cite
|
Sign up to set email alerts
|

Heroes and Holidays: The Status of Diversity Initiatives at Liberal Arts College Libraries

Abstract: Studies about diversity initiatives in academic libraries have primarily focused on large research libraries. But what kinds of diversity work occur at smaller libraries? This study examines the status of diversity initiatives, especially those aimed at students, at national liberal arts college libraries. Results from a survey of library directors reveal that, while diversity programming happens informally at most libraries, and while diversity is valued by library directors, diversity work has not been prior… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
7
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 12 publications
1
7
0
1
Order By: Relevance
“…Collaborating with colleagues from other departments significantly increased the potency of the messages I needed to deliver when I was the only one who had knowledge of reported incidents. This experience echoes that of other librarians collaborating within their institutions on DEI initiatives, as shown in Gilbert’s (2016) research and reported by individual librarians (Love, 2007; Switzer, 2008; Edwards, 2010; Leadley and Ryan, 2015).…”
Section: Advancing and Maintaining An Inclusive Campus Climatesupporting
confidence: 73%
“…Collaborating with colleagues from other departments significantly increased the potency of the messages I needed to deliver when I was the only one who had knowledge of reported incidents. This experience echoes that of other librarians collaborating within their institutions on DEI initiatives, as shown in Gilbert’s (2016) research and reported by individual librarians (Love, 2007; Switzer, 2008; Edwards, 2010; Leadley and Ryan, 2015).…”
Section: Advancing and Maintaining An Inclusive Campus Climatesupporting
confidence: 73%
“…This report acknowledges the robust and various conversations about diversity reflected in demographic professional representation, 3 holdings, 4 and mission and values statements 5 at academic and public libraries and archives. 6 In this report, and given the thematic emphases of the LVEHC, the authors consider diversity especially in terms of race, ethnicity, and histories of migration.…”
mentioning
confidence: 85%
“…A reliance on noble rhetoric and opaque organizational objectives that fail to gain traction tends to be commonplace with DEIA initiatives. Too often, the research indicates that many individuals verbalize the will to engage in meaningful DEIA work (Leslie et al 2021) yet fail to operationalize DEIA efforts beyond celebrating (often dead) heroes and holidays (Gilbert 2016). The work of DEIA must not stop with verbal expressions.…”
Section: Foregrounding Franklin's Quote To Create the "Frank-lin Model Of Deia"mentioning
confidence: 99%